A Systematized Review of Professional Employment Following Thoracic Transplantation. (March 2022) - Jobst, Stefan; Schaefer, Jonas; Kleiser, Christina; Kugler, Christiane
Introduction: Acknowledging the evolved landscape in thoracic transplantation, professional employment becomes an important outcome measure to quantify the success of this costly procedure. Objective: We aimed to assess rates of and characterize factors associated with professional employment in patients following thoracic transplantation, and create an evidence-base on the relationship between professional employment and relevant outcome parameters. Methods: We systematically searched Medline, Cinahl, and GoogleScholar to identify studies published between 1998 and 2021 reporting on professional employment following heart and lung transplantation. Results: Twenty-two studies from 11 countries with varying sample sizes (N = 27; 10 066) were included. Employment rates ranged from 19.7% to 69.4% for heart, and from 7.4% to 50.8% for lung transplant recipients. Most frequently reported positively associated factors with employment after transplant were younger age, higher education, and history of pretransplant employment. Longer duration of unemployment prior to transplantation and Medicaid coverage were the most frequently reported negatively associated factors. Relationships between professional employment and clinical outcomes included lower rates of acute and chronic rejection, less infection episodes, and better quality of life among working patients; one study reported a lower 5-year-mortality rate. Reasons not to work were "physical or mental health-related, " "employment-related, " "financial reasons, " and "lifestyle choices." Discussion: Substantial proportions of patients following thoracic transplantation are not professionally employed, potentially diminishing the success of transplantation on individual and societal levels. Considering adverse clinical outcomes in employed transplant recipients were low, more efforts are needed to identify modifiable factors for employment in these populations.